Advancements in Applications of Microbiology and Bioinformatics in Pharmacology: Life Sciences-Pharmacology - Mr. A. Harishchander, Guest Editor (International Journal of Life Science and Pharma Research, 2020)
This special issue is highly related to Microbiology and Bioinformatics application for pharmacology and its usage in medical and health care systems towards providing leads for molecular development and an initiative in Basic science to perform advanced research in areas like the virtual patient and CRISPER Human. Also, it focuses on the integration of machine learning algorithms to mankind. In addition to the basic science involved in Microbiology, Bioinformatics and Pharmacology, the advancements in the current stage of applying the schemas of artificial intelligence (AI) in basic sciences are also focused in this issue. Artificial intelligence in the diagnosis of health care is the requirement for the current era of Digital Genomics. This special issue focuses on both basic science and advanced developments in the current era of Digital Genomics. The articles published in this special issue will certainly bring a positive effect for the development of health care systems and scientific leads to develop molecules with the available resources enhance the maximum utilization of scientific knowledge to potentiate diagnosis and therapy in health care.